2003
DOI: 10.1109/tpami.2003.1251148
|View full text |Cite
|
Sign up to set email alerts
|

Face recognition in hyperspectral images

Abstract: Abstract-Hyperspectral cameras provide useful discriminants for human face recognition that cannot be obtained by other imaging methods. We examine the utility of using near-infrared hyperspectral images for the recognition of faces over a database of 200 subjects. The hyperspectral images were collected using a CCD camera equipped with a liquid crystal tunable filter to provide 31 bands over the near-infrared (0.7m-1.0m). Spectral measurements over the near-infrared allow the sensing of subsurface tissue stru… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
12
0

Year Published

2005
2005
2023
2023

Publication Types

Select...
4
3
2

Relationship

0
9

Authors

Journals

citations
Cited by 316 publications
(12 citation statements)
references
References 23 publications
0
12
0
Order By: Relevance
“…While spectral signatures have little dependence on skin temperature over the NIR region, measured radiance in the thermal infrared (8 to 12 μm) has a strong dependence on skin temperature. 202 MHSI can also be limited by the cost of HSI imaging systems and by the ability to extract relevant information from large datasets.…”
Section: Discussionmentioning
confidence: 99%
“…While spectral signatures have little dependence on skin temperature over the NIR region, measured radiance in the thermal infrared (8 to 12 μm) has a strong dependence on skin temperature. 202 MHSI can also be limited by the cost of HSI imaging systems and by the ability to extract relevant information from large datasets.…”
Section: Discussionmentioning
confidence: 99%
“…11 All images have 31 spectral bands with center wavelengths separated by 0.01 μm over the NIR (0.7 to 1.0 μm). 11 All images have 31 spectral bands with center wavelengths separated by 0.01 μm over the NIR (0.7 to 1.0 μm).…”
Section: Methodsmentioning
confidence: 99%
“…The method to obtain the spectral reflectance from the image measurements is provided by Pan et al 11 Based on previous work 11 that showed that skin provides the best recognition results, we use skin regions for the extraction of spectral features. Several regions are chosen for feature extraction.…”
Section: Featuresmentioning
confidence: 99%
“…However, limited by the existing imaging techniques, higher spectral resolution often comes at the expense of lower spatial resolution. This might limit the applications of HSI in the fields of remote sensing [1,2,3], classification [4,5,6], and etc [7,8].…”
Section: Introductionmentioning
confidence: 99%